Status of Organizational Justice Dimensions: Evidence from Banks and Insurance Companies - Parajuli, Dilip; Shrestha, Prakash (The Batuk, 2024)
This study examines the current state of organizational justice based on the perspectives of managers and employees in Nepalese banks and insurance companies. It also examines the differences in organizational justice dimensions. It uses a survey method, with questionnaires serving as the major tool. A total of 480 questionnaires (30 in each of the 16 institutions, including 8 commercial banks and 8 insurance companies) were distributed, and 327 (68.10%) of the completed and returned copies were used for the study. The findings demonstrate that employees generally rate their job schedule as adequate, their income as appropriate, and their workload and job requirements as reasonable. The findings indicate that employees have a positive perception of procedural justice. They also indicate that employees believe management treats them with respect, dignity, and honesty. The results suggest that the three dimensions of organizational justice differ significantly among Nepalese respondents. However, all three justice dimensions are crucial for organizational success. Therefore, companies' primary priorities should be to improve organizational justice. They should motivate employees to put up a significant effort for the benefit of the companies.